KONSTRUKSI EXPERT ADVISOR DENGAN FIBONACCI MONEY MANAGEMENT STRATEGY MENGGUNAKAN INDIKATOR ICHIMOKU CLOUD PADA TRADING CRUDE OIL (XTIUSD) DI METATRADER 5 - Iqbal, Muhammad; Rahman, Haikal (Universitas Persada Indonesia YAI, 2025)
Crude Oil (XTIUSD) commodity trading offers significant opportunities but isaccompanied by high volatility and the challenge of trader psychological bias. Tradingautomation through Expert Advisors (EAs) is a solution to overcome inconsistency andimprove execution discipline. This study aims to construct an Expert Advisor on theMetaTrader 5 platform that integrates trading signals from the Ichimoku Cloud indicatorwith the Fibonacci Money Management strategy to optimize XTIUSD trading. This studyuses the Research and Development (R&D) method with a V-Model approach. The EA'sperformance was evaluated through two scenarios (H1 and H4 timeframes) usingbacktesting on 4 years of historical data (January 1, 2021 – December 31, 2024) andvalidated with real-time testing (August 22 – September 22, 2025). The results of the studyshow significant discrepancies: Scenario 1 (H1) was very profitable in backtesting (ProfitFactor 1.46) but failed in real-time testing (Profit Factor 0.04), indicating a high potentialfor overfitting. Scenario 2 (H4) shows more stable backtesting performance (Profit Factor1.72) and is profitable in real-time testing, albeit with a very limited sample size (1transaction). The main conclusion is that the EA was successfully constructed, and the H4timeframe (Scenario 2) proved to be more stable. However, the main weakness of thedeveloped system is its strong dependence on bullish market conditions, where bothscenarios only execute buy positions (long trades), making it not robust for bearish orsideways market conditions